Acute dissection of the coexistent abdominal aortic aneurysm - Naoto Fukunaga; Akio Shimoji; Toshi Maeda; Otohime Mori; Kosuke Yoshizawa; Nobushige Tamura (Annals of Vascular Surgery - Brief Reports and Innovations, 2022)
We present a 76-year-old female who complained about severe back pain. Contrast-enhanced computed tomography revealed a 5-cm abdominal aortic aneurysm with a large primary entry causing retrograde type B aortic dissection limited to the abdominal lesion. Emergency graft replacement of abdominal aorta with a bifurcated vascular graft was successfully performed due to the persistent symptom and extension of aortic dissection into the thoracic lesion. Our case was unique in terms of abdominal aortic aneurysm complicating by acute dissection, but life-threatening. This combination should consider the emergency surgery to avoid rupture.